2021
DOI: 10.3390/ani11102906
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Sequencing in Different Types of Goat Skeletal Muscles Reveals Genes Regulating Muscle Development and Meat Quality

Abstract: Domestic goats are commonly reared for meat and milk production in several regions of the world. However, the genetic mechanism underlying muscle development and meat quality of goats is limited. Therefore, the aim of this study was to identify known and novel genes regulating muscle development and meat quality of goats using second- and third-generation sequencing technologies. To achieve this, the meat quality and transcriptomes of longissimus dorsi (LD) and biceps femoris (BF) muscle tissues of Lingqiu Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…In this study, a total of 9,845 novel genes and 66,989 isoforms were identified by PacBio seq, and nearly half of the gene loci were equal to or greater than 3Kb. Consistently with previous studies, PacBio identified more long transcripts than reference annotated transcripts [24,25]. In addition, numerous novel lncRNA was predicted from the Iso-seq.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, a total of 9,845 novel genes and 66,989 isoforms were identified by PacBio seq, and nearly half of the gene loci were equal to or greater than 3Kb. Consistently with previous studies, PacBio identified more long transcripts than reference annotated transcripts [24,25]. In addition, numerous novel lncRNA was predicted from the Iso-seq.…”
Section: Discussionsupporting
confidence: 88%
“…Sequencing and data analysis procedures are shown in Figure 1 . Library preparation and sequencing followed previously reported methods with slight modifications [ 10 ]. Total RNA was extracted from frozen adipose tissues using TRIzol (Takara, Dalian, China) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gene transcripts undergo diverse splicing to generate various isoforms. With the commercialization of sequencing platforms and the reduced sequencing costs, transcriptome sequencing technology has found widespread application in animal transcriptome studies, including pigs [ 7 ], chickens [ 8 ], beef cattle [ 9 ], goats [ 10 ], and sheep [ 11 ]. Previous studies on sheep fat metabolism have primarily focused on short-read RNA-seq data from second-generation sequencing platforms [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mass accounts for 40–60% of the body weight of mammals, and skeletal muscle is considered the most important tissue for producing meat livestock. Many studies have focused on the growth and development of skeletal muscle to identify relevant biological mechanisms underlying meat yield and quality and offer the possibility of improving growth traits in goats [ 6 , 7 , 8 , 9 ]. In addition, skeletal muscle development in mammals can be divided into prenatal and postnatal stages; the number of muscle fibers increases before birth and the volume of muscle fibers increases after birth [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing is a high-throughput sequencing method for characterizing gene expression in specific tissues that provides accurate counts of transcripts to measure relative expression and to discover new exons or genes [ 16 ]. This approach is widely used for research on gene expression profiles revealing muscle growth and development, and the transcriptome profiles of different breeds and muscle tissues are becoming increasingly clear in goats [ 6 , 7 , 8 , 17 , 18 ]. Some functional differentially expressed genes (DEGs) from different kinds of materials in KEGG pathways, such as the Jak-STAT signaling pathway [ 18 ], MAPK signaling pathway [ 19 ], and PI3K-Akt signaling pathway [ 7 , 20 ], have been found to play crucial roles in muscle growth and development in goats.…”
Section: Introductionmentioning
confidence: 99%